Flood Disaster Mitigation Management by The Regional Disaster Management Agency (BPBD), Mojokerto District, Indonesia - Ellza Nathania Christy; Muhammad Agus Muljanto (Publik : (Jurnal Ilmu Administrasi), 2025)
Floods remain one of the most frequent natural disasters in Indonesia, causing significant impacts on communities, infrastructure, and local economic activities. Areas located near riverbanks and low-lying regions are particularly vulnerable, making effective disaster mitigation an essential component of risk reduction and community resilience. This study aims to understand and analyze flood disaster mitigation management implemented by the Regional Disaster Management Agency (BPBD) in Kedunggempol Village, Mojosari District, Mojokerto Regency. The research employs a qualitative method with a case study approach. Data were collected through interviews, observations, documentation, and literature review. The findings reveal that the implementation of non-structural mitigation measures, including training, public education, and early warning systems, remains limited, while community participation has not been fully optimized. BPBD has also not completely established local disaster management institutions or provided mitigation incentives for residents. Regarding structural mitigation, Kedunggempol Village only possesses levees that are often damaged and remain in unstable condition, along with several non-engineered buildings that have been elevated independently by the community. The study concludes that although both structural and non-structural mitigation efforts have been implemented, their effectiveness remains suboptimal. Therefore, stronger policy support, improved inter-agency coordination, and broader community involvement are necessary to enhance disaster preparedness and reduce flood risks in the area.